2018
DOI: 10.1055/s-0038-1647248
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Assessment of Intra-Articular Structures in the Canine Stifle Joint after Implantation of a Titanium Tibial Plateau Levelling Osteotomy Plate

Abstract: In selected TSE sequences, MRI allows evaluation of critical intra-articular structures after titanium TPLO plate implantation. Further investigations with confirmed stifle pathologies in dogs are required, to evaluate the accuracy of MRI after TPLO in clinical cases in this context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Currently, apart from the manufacturer's instructions, there are no guidelines regarding the positioning of the dog for knee imaging. In other articles, dogs were placed in the dorsal (2,5,12,23,24,32,40,43,44) lateral (4,11,36,37) or bridge position (15).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, apart from the manufacturer's instructions, there are no guidelines regarding the positioning of the dog for knee imaging. In other articles, dogs were placed in the dorsal (2,5,12,23,24,32,40,43,44) lateral (4,11,36,37) or bridge position (15).…”
Section: Discussionmentioning
confidence: 99%
“…Feichtenschlager and colleagues showed that selected sagittal turbo spin echo sequences of MRI enabled interpretation of most soft tissue, osseous and cartilage structures without detrimental effects of susceptibility artefact distortions in canine stifles after implanting a tibial plateau levelling osteotomy titanium plate. 3 Although further investigations are required, the improved clinical accuracy in diagnosing soft tissue complications such as late meniscal injury will be valuable.…”
mentioning
confidence: 99%